A Formal Model of an Argumentative Dialogue in the Management of Emotions - Kacprzak, Magdalena; Sawicka, Anna; Zbrzezny, Andrzej; Rzeńca, Krzysztof; Żukowska, Katarzyna (Logic and Logical Philosophy, 2017)
In this research, we focus on designing an interactive tool which will be used as an aid in learning how to manage emotions during argumentative dialogues. To this end, a collection of examples illustrating the typical human’s reactions was collated and used to explain mechanisms that appear in dialogues. We present a theoretical background of the project, i.e., a formal system to represent the change of intensity of emotions in argumentative dialogues. We rely here on persuasive dialogue games. A formal language for expressing properties of protocols for dialogues with emotional reasoning is proposed. We suggest that awareness of emotions improves communication between parents and children, and that it is an important element of both raising communication skills in adults and development of communication skills in children.